A distributed frontotemporal network underlies gamma-band synchronization impairments in schizophrenia patients - Koshiyama, Daisuke; Miyakoshi, Makoto; Joshi, Yash B.; Molina, Juan L.; Tanaka-Koshiyama, Kumiko; Sprock, Joyce; Braff, David L.; Swerdlow, Neal R.; Light, Gregory A. (Neuropsychopharmacology (New York, N.Y.), 2020)
Synaptic interactions between parvalbumin-positive γ-aminobutyric acid (GABA)-ergic interneurons and pyramidal neurons evoke cortical gamma oscillations, which are known to be abnormal in schizophrenia. These cortical gamma oscillations can be indexed by the gamma-band auditory steady-state response (ASSR), a robust electroencephalographic (EEG) biomarker that is increasingly used to advance the development of novel therapeutics for schizophrenia, and other related brain disorders. Despite promise of ASSR, the neural substrates of ASSR have not yet been characterized. This study investigated the sources underlying ASSR in healthy subjects and schizophrenia patients. In this study, a novel method for noninvasively characterizing source locations was developed and applied to EEG recordings obtained from 293 healthy subjects and 427 schizophrenia patients who underwent ASSR testing. Results revealed a distributed network of temporal and frontal sources in both healthy subjects and schizophrenia patients. In both groups, primary contributing ASSR sources were identified in the right superior temporal cortex and the orbitofrontal cortex. In conjunction with normal activity in these areas, schizophrenia patients showed significantly reduced source dipole density of gamma-band ASSR (ITC > 0.25) in the left superior temporal cortex, orbitofrontal cortex, and left superior frontal cortex. In conclusion, a distributed network of temporal and frontal brain regions supports gamma phase synchronization. We demonstrated that failure to mount a coherent physiologic response to simple 40-Hz stimulation reflects disorganized network function in schizophrenia patients. Future translational studies are needed to more fully understand the neural mechanisms underlying gamma-band ASSR network abnormalities in schizophrenia.